Reflections on Educational Issues among Modern Language Students - Anna Carolina Peñaloza; Jhonatan Vasquez Guarnizo (HOW)
The following pedagogical proposal seeks to understand what types of reflections Modern Languages students reveal about educational issues when analyzing artwork within their context. We worked with twelve Modern Languages students in their fifth and sixth semester at a public university in Colombia. The students began by analyzing four murals located within the university. Then, they created their own artwork and provided reflections on each other’s pieces of art. The findings showed that the students first began analyzing visual aspects of the murals and artwork, followed by the educational issues represented in each piece. As a common theme, the students reflected on the idea that working together yields a diversity of solutions. Finally, the students demonstrated that they could benefit from reflective practices despite not having started their teaching practicum.